Engineering mathematics through applications - Singh, Kuldeep. 4 0 16; 5 (Basingstoke, Hampshire : Palgrave Macmillan, 2011)
Teaches maths in a step-by-step fashion, ideal for students in first-year engineering courses. Includes hundreds of examples and exercises, mainly set in an applied engineering context -- Back cover.
1. Engineering formulae 2. Visualizing engineering formulae 3. Functions in engineering 4. Trigonometry and waveforms 5. Logarithmic, exponential and hyperbolic functions 6. Differentiation 7. Engineering applications of differentiation 8. Integration 9. Engineering applications of integration 10. Complex numbers 11. Matrices 12. Vectors 13. First order differential equations 14. Second order linear differential equations 15. Partial differentiation 16. Probability and statistics.
Includes index.
Keywords: 2 -- 0; 6; Engineering mathematics. -- 20; 20; 2